Fast and adaptive dynamics-on-graphs to dynamics-of-graphs translation - Zhang, Lei; Chen, Zhiqian; Lu, Chang-Tien; Zhao, Liang (Frontiers in Big Data, 2023)
Numerous networks in the real world change with time, producing dynamic graphs such as human mobility networks and brain networks. Typically, the "dynamics on graphs" (e.g., changing node attribute values) are visible, and they may be connected to and suggestive of the "dynamics of graphs" (e.g., evolution of the graph topology). Due to two fundamental obstacles, modeling and mapping between them have not been thoroughly explored: 1) the difficulty of developing a highly adaptable model without solid hypotheses, and 2) the ineffectiveness and slowness of processing data with varying granularity. To solve these issues, we offer a novel scalable deep echo-state graph dynamics encoder for networks with large time duration and sizes. A novel neural architecture search (NAS) technique is then proposed and tailored for the deep echo-state encoder to ensure strong learnability. Extensive experiments on synthetic and actual application data illustrate the proposed method's exceptional effectiveness and efficiency.